Internal auditing - public sector of the Sarawak state govermen - Jeman, bin Udin (2002)
The main are of concerns or problems to investigate are whether the public sector of the Sarawak state government are moving toward a more professional approach in the current practices of internal auditing and simultaneously to find out the reason why the Institute of Internal Auditor, Malaysia (IIAM) are not eager to organize courses or seminars in Sarawak.